Metabolic efficiency in a supramaximal treadmill running test does not directly determine 400-m sprint performance - Muratomi, K.; Furuhashi, Y.; Ushirooka, N.; Kanno, K.; Tanigawa, S.; Maemura, H. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: The 400-m sprint is a complex event requiring contributions from the phosphagen, glycolytic, and oxidative energy systems. This study investigated the relation between metabolic energy expenditure during short-term supramaximal running and 400-m sprint performance. METHODS: Sixteen male sprinters performed a treadmill test at approximately 90% of their mean 400-m sprint speed. Energy expenditure was estimated based on three components: the fast component of excess post-exercise oxygen consumption (phosphagen system), the difference between peak and baseline blood lactate concentrations (glycolytic system), and oxygen uptake above the baseline level (oxidative system). RESULTS: No significant correlations between total or individual energy expenditures (phosphagen, glycolytic, oxidative) and 400-m sprint time (r=-0.216-0.405, P=0.119-0.423), with variability in individual energy distribution strategies. CONCLUSIONS: These findings suggest that metabolic efficiency alone does not directly determine 400-m sprint performance. Instead, they emphasize the importance of personalized training programs that focus on optimizing individual energy system utilization and pacing strategies rather than solely enhancing metabolic efficiency.